Two Solovyovs: uncle and nephew - Nemeth, Thomas (Studies in East European thought, 2025)
The next year, his wife, who remained in Saratov, wrote that she had taken up with another man, a factor in this severance of his marriage being Sergey’s “enthusiasm” for a reunification of the churches. Accepting the message of his uncle, Sergey first became a Uniat and then after some considerable vacillation in the early 1920s he converted to Catholicism.6 Quite possibly, he briefly rejoined Orthodoxy in 1922-1923 after personal relations with Catholic authorities soured coupled with his reluctance to fully accept papal infallibility, and further, the refusal of the Catholic Church to recognize ancient Russian saints. Sergey’s nerves and general medical condition were no match for the interrogation methods of the OGPU.10 Although, of course, we cannot be certain what transpired while in police custody, accounts corroborate that a police informant who enjoyed Sergey’s confidence played his expected part. Other sources have given the sentence as having different durations.11 In any case, Sergey’s mental health soon sharply deteriorated, and in October 1931 he was released from his sentence.